Robotic pancreatoduodenectomy at an experienced institution is not associated with an increased risk of post-pancreatic hemorrhage. Issue 5 (May 2018) - Magge, Deepa; Zenati, Mazen; Lutfi, Waseem; Hamad, Ahmad; Zureikat, Amer H.; Zeh, Herbert J.; Hogg, Melissa E.
Abstract: Background: Postpancreatectomy hemorrhage (PPH) is a serious and life threatening complication following pancreaticoduodenectomy. The objective was to determine whether PPH incidence is elevated in a series of robotic pancreatoduodenectomy (RPD) from a high-volume institution and if video review can identify technical factors associated with PPH. Methods: A retrospective review of RPDs from October 2008 to March 2016 was performed. PPH was classified by established international criteria. Technical factors from RPD resection were ascertained using video analysis. Clinical and technical variables were analyzed using multivariate analysis. Results: Of 400 patients who underwent RPD PPH occurred in 19 (4.8%) and 168 (42%) had videos available to review. The technique of RPD was consistent but a falciform flap was performed routinely after RPD#181 and flaps were performed less (37.5% vs 75%) in the pseudoaneurysm group ( p  = 0.033). On univariate analysis of technical variables, gastroduodenal artery (GDA) mishandling and suture ligation were positive predictors of pseudoaneurysm formation while falciform flap placement was a negative predictor (all p  < 0.05). GDA suture ligation remained significant on multivariate analysis ( p  = 0.006). A negative relationship was found between pseudoaneurysm occurrence and time ( ρ  = −0.533; p  < 0.05). Conclusions: PPH in a large series of RPD is similar to reported rates in historical open control series; however, pseudoaneurysm is less common with increasing experience. Video review is a useful tool in identifying technical variables during in RPD.